PERANCANGAN RUANG TERBUKA PUBLIK DENGAN KONSEP PLACEMAKING DI BAWAH JEMBATAN PASUPATI - Riadi, Aqila Syahira; Putra, Bagas Dwipantara (Pranatacara Bhumandala: Jurnal Riset Planologi, 2025)
Public open spaces play a significant role in improving the quality of life of people in urban areas. Its existence can be utilized as a place for social interaction, community activities, and recreational facilities. This research aims to redesign the area under Pasupati Bridge, Bandung City, using a placemaking approach, in order to create a public open space that is meaningful, has a strong identity, and is favored by its users. To achieve this goal, this research sets several objectives, namely identifying the normative principles of placemaking, assessing the potential and problems of the area, and redesigning the study area with this approach. The research is qualitative in nature, using descriptive and normative approaches, and relying on field observation and literature study as data collection methods. The results show that the area has various utilization potentials, but is also faced with a number of problems. Based on this, a design concept was formulated that aims to realize a friendly, active, and sustainable public open space.